Festival de Stad. (Arnhem: Stichting Festival, 1983)
Huisman, Gerard, Corstiansen, Boudewijn ; van Westen, Jeroen ; Blaauw, Kerstjan ; Garcia, David ; Janselijn, Han ; van Haasteren, Cor ; Boezem, Marinus ; Baren, Peter ; Gerritsen, Ad ; Arts, Arno ; etc.
Festival de Stad, Arnhem, 14 mei - 3 juni 1983
boek